Treatment of Infantile Spasms with Valproic Acid - Taslim S. Soetomenggolo (Indonesian Pediatric Society, 1988)
During 2 years (1985- 1986), 12 patients with infantile spasms were treated at the Department of Child Health, Dr. Cipto Mangunkusumo General Hospital, Jakarta. The diagnosis of infantile spasms was based on the specific clinical manifestation and the specific EEG pattern. -Head CT Scan was done to look for abnormalities of the brain. Eleven (91.6%) of the 12 patients had suffered from neurological deficit before treatment was started. Eleven patients suffered from developmental retardation one patient suffered from cerebral palsy, and 5 patients had microcephaly. In nine (75%) of the 12 patients, the EEG showed hypsarrhythmia, and in 3 (25%) multi focal spikes were found. All of the 12 patients were treated with the combination of ACTH/dexamethasone and valproic acid. Excellent results were found in 8 (66. 7%) patients, and good in 4 (33.3%). All of the EEG abnormalities disappeared after treatment.